Documenting Arts. Between two Poles: an Archive of Paper and Objects and a Digital Born Archive - Zanella, Francesca (InCID: Revista de Ciência da Informação e Documentação, 2016)
The essay intends to offer a contribution to the archival studies through two study cases that have different stories and diversified nature: the CSAC (Study Center and Research on Communication), and MoRE (Museum of Refused and Unrealised Art Projects – http://www.moremuseum.org/omeka/-.). These are two archives devoted to contemporary art and design practices. CSAC is mainly devoted to italian art and design of the XX century; MoRE is an archive of unrealised works of art from the second half of the XX century till today. CSAC is an archive of paper, while MoRE is a digital repository. Finally both the archives have a common objective: promoting the research on contemporary art practices through the collecting and cataloguing of works of art and items of the design process.